2019
DOI: 10.1111/exd.13919
|View full text |Cite
|
Sign up to set email alerts
|

Matrix remodelling and MMP expression/activation are associated with hidradenitis suppurativa skin inflammation

Abstract: Hidradenitis suppurativa/acne inversa (HS) is a chronic, inflammatory, recurrent, debilitating skin disease of the hair follicle, associated with considerable tissue remodelling. Although abnormal cytokine expression was detected both in perilesional and in uninvolved skin, up to now there is no model allowing a better understanding of the implicit inflammatory mechanisms in HS. The aim of this study was to investigate the inflammatory response in HS skin by mean of an ex vivo model culture. To that purpose, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
(39 reference statements)
4
41
0
Order By: Relevance
“…Existing studies in HS demonstrate intriguing evidence of fibroblast‐related pathways being activated in lesional tissue. Elevations in IL‐1β, IL‐6, IL‐8, MMP2 and MMP9 as well as extensive matrix remodelling are core manifestations of HS . IHC studies have identified co‐localization of MMP2 to dermal fibroblasts .…”
Section: The Inflammatory Signature Of Hidradenitis Suppurativa Suggementioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies in HS demonstrate intriguing evidence of fibroblast‐related pathways being activated in lesional tissue. Elevations in IL‐1β, IL‐6, IL‐8, MMP2 and MMP9 as well as extensive matrix remodelling are core manifestations of HS . IHC studies have identified co‐localization of MMP2 to dermal fibroblasts .…”
Section: The Inflammatory Signature Of Hidradenitis Suppurativa Suggementioning
confidence: 99%
“…HS significantly differs to other chronic inflammatory dermatose due to the development of hypertrophic scarring and dermal tunnels . The development of which suggest that fibroblastic stromal cells (including myofibroblasts, fibroblasts, pericytes etc) may be involved in the development and progression of disease . The recent investigations by Sanchez et al experimentally demonstrate that biologically active peptides and inflammatory mediators from the extracellular matrix (ECM) engage in inflammatory crosstalk with keratinocytes in HS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sanchez et al produced an ex-vivo cultured skin model for HS (25) and observed the specimens through immunohistochemistry. MMP-2 and MMP-9 were elevated in lesional skin.…”
Section: Mmp-2 and Mmp-9 In Cultured Biopsies Of Lesional And Peri-lementioning
confidence: 99%
“…These cells also express IL‐17 and IL‐23 which may support lymphocyte activation and/or changes to hair follicle biology . Innate cells, non‐immune cells, extracellular matrix remodelling, cytokines, chemokines and hormones in the vicinity may all have an impact on the development of lymphocytic scaring alopecias.…”
Section: Scarring Alopeciamentioning
confidence: 99%